Quality Analysis of Lots of Wheat Harvested from Areas Affected by Extreme Drought - Ciprian Petrișor PLENOVICI; Constanța Laura AUGUSTIN (ZUGRAVU); Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2021)
In Romania, the agricultural year 2019-2020 was marked by an accentuated pedological drought in almost all regions of the country, thus affecting the wheat crops in all their stages. The lack of precipitations during the sowing optimal  season  delayed the sowing itself,  led to a decrease of sprout and of twinning and generated a poor quality and diminished  the harvest. The climatological factor had a negative economic impact directly on the farmers thus the population’s food security would have been highly affected  in the absence of the Government intervention with granting subsidies. This study highlights the quality of some wheat lots from different agricultural areas affected by extreme drought in relation to the quality conditions imposed by the Grading National System for Seeds for Consumption.
Keywords: Drought; Wheat; Quality; Romanian Wheat